Raymond Gibson (1938–2023): in memoriam - Chernyshev, Alexei V.; Alfaya, José E. Fernández; Anadón, Nuria; Andrade, Sónia C. S.; Bartolomaeus, Thomas; Döhren, Jörn Von; Fernández-Álvarez, Fernando Ángel; Giribet, Gonzalo; Junoy, Juan; Kajihara, Hiroshi; Kem, William R.; Kuris, Armand; et al. (Zootaxa, 2023)
N